1988
DOI: 10.3354/dao004199
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing monoclonal antibodies recognize antigenic variants among isolates of infectious hematopoietic necrosis virus

Abstract: Neutralizing monoclonal antibodies were developed against strains of infectious hematopoietic necrosis virus (IHNV) from steelhead trout Salmo gajrdneri in the Deschutes River of Oregon, chinook salmon Oncorhynchus tshawytscha in the Sacramento h v e r of California, and rainbow trout Salmo gairdneri reared in the Hagerman Valley of Idaho. USA. These antibodies were tested for neutralization of 12 IHNV isolates obtained from salmonids in Japan, Alaska, Washington, Oregon, California, and Idaho. The antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 9 publications
1
48
0
Order By: Relevance
“…For other rhabdoviruses, such as rabies and vesicular stomatitis virus, the virion glycoprotein (G) molecular weights vary anlong strains, and pathogenicity of rabies can be determined with G-specific monoclonal antibodies (Dietzschold et al 1983). While differences in G could not be detected among strains of IHNV with polyvalent antisera (Engelking et al 1991), they were detected with G-specific monoclonal antibodies (Winton et al 1988, Ristow & Arnzen de Avila 1991) but virulence of these isolates was not tested. Recent studies comparing G gene nucleic acid sequences of IHNV isolates from California, Oregon, Washington and Idaho indicated this gene was highly conserved (J. R. Winton, U.S.…”
Section: Discussionmentioning
confidence: 99%
“…For other rhabdoviruses, such as rabies and vesicular stomatitis virus, the virion glycoprotein (G) molecular weights vary anlong strains, and pathogenicity of rabies can be determined with G-specific monoclonal antibodies (Dietzschold et al 1983). While differences in G could not be detected among strains of IHNV with polyvalent antisera (Engelking et al 1991), they were detected with G-specific monoclonal antibodies (Winton et al 1988, Ristow & Arnzen de Avila 1991) but virulence of these isolates was not tested. Recent studies comparing G gene nucleic acid sequences of IHNV isolates from California, Oregon, Washington and Idaho indicated this gene was highly conserved (J. R. Winton, U.S.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic pathology induced by the Oregon and California isolants, Types 1 and 3 IHNV strains, appeared the same but was less severe and involved La Patra et a1 : Compara P ltive pathogenesis of IHNV 111 P sons of IHNV isolants using monoclonal antibodies directed against the glycoprotein (G) tended to group isolants more by geographic location rather than virulence (Winton et al 1988). For other rhabdoviruses such as rabies, it has been shown with G-specific monoclonal antibodies that pathogenicity is dependent on the presence of an antigenic determinant on the Gprotein (Dietzschold et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown differences in the molecular weights of virion structural proteins (Leong et al 1981) and have allowed the separation of 71 isolants into 5 types (Hsu et al 1986). Winton et al (1988) used 3 monoclonal antibodies and were able to separate 12 IHNV isolants into 4 groups. In this study the virulence and pathogenesis of 3 of the most commonly encountered strains (Types 1, 2 and 3) of IHNV are compared in rainbow trout.…”
Section: Introductionmentioning
confidence: 99%
“…It was prepared to an IHNV strain isolated from steelhead trout at Round Butte, Oregon, and was found to neutralize ten different IHNV isolates (Winton et al, 1988).…”
Section: Antisera and Monoclonal Antibodiesmentioning
confidence: 99%